Accidental cannabis intoxication in two young children: clinical presentation and toxicokinetics - a case series - Cafaro, Alessia; Pigliasco, Federica; Barco, Sebastiano; Negro, Ilaria; Piccotti, Emanuela; Manfredini, Luca; Mahameed, Samir; Bandettini, Roberto; Debbia, Carla; Mattioli, Francesca; Cangemi, Giuliana (Frontiers in Pharmacology, 2025)
Accidental exposure to edible cannabis products in children is an increasing public health concern. The clinical presentation is often nonspecific, which can delay diagnosis and lead to inappropriate management. Toxicological screening is therefore essential for accurate diagnosis and appropriate treatment. We report the toxicokinetic (TK) profiles of delta-9-tetrahydrocannabinol (THC) and cannabidiol (CBD) following unintentional ingestion of cannabis in two pediatric cases, aged 12 and 15 months, respectively. Plasma concentrations of THC and CBD were measured using a validated liquid chromatography–tandem mass spectrometry (LC-MS/MS) method. THC was consistently detected in all plasma samples collected (four per patient), with highest measured concentrations of 45.0 μg/L in Case 1 and 54.7 μg/L in Case 2. CBD was not detected in Case 1, whereas in Case 2 it was measurable only in the first plasma sample, at a concentration of 1.11 μg/L. Non-compartmental analysis (NCA) of the THC concentration–time data enabled calculation of the TK profiles in both cases. The elimination rate constant (kel) was 0.013 h−1 in Case 1 and 0.031 h−1 in Case 2, corresponding to an half-life (t½) of 52.5 and 21.7 h, respectively. Given the variability and unpredictability of THC/CBD TK monitoring drug levels over time is crucial for managing intoxications in children.